2014
DOI: 10.1590/1983-1447.2014.01.37887
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students and mental health education in primary care

Abstract: The University of Sao Paulo School of Nursing (EEUSP) went through a period of transition from undergraduate syllabus between the years 2009 and 2010. This change was made to integrate basic and clinical cycles and to reduce fragmentation of the disciplines. The mental health nursing education was included in many modules including the primary care. This qualitative study aimed to identify how the service offered to people with mental illness was performed by 20 undergraduate students in the context of primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
13

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 6 publications
(5 reference statements)
0
4
0
13
Order By: Relevance
“…(11,13,(15)(16) Estágios, atividades práticas ou visita de campo ajudam a visualizar melhor o trabalho e promovem uma formação mais completa. (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Possibilidade de desenvolvimento de competências e habilidades terapêuticas no campo prático. (10,(12)(13)(14)(15)(16)(17)(18)(19) Aspectos de fragilizam a formação em saúde mental A carga horária das disciplinas não é adequada.…”
Section: Eixo Temático Subtemasunclassified
“…(11,13,(15)(16) Estágios, atividades práticas ou visita de campo ajudam a visualizar melhor o trabalho e promovem uma formação mais completa. (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Possibilidade de desenvolvimento de competências e habilidades terapêuticas no campo prático. (10,(12)(13)(14)(15)(16)(17)(18)(19) Aspectos de fragilizam a formação em saúde mental A carga horária das disciplinas não é adequada.…”
Section: Eixo Temático Subtemasunclassified
“…Nursing students and mental health education in primary care (26) To identify how care for people with mental illness was performed by 20 undergraduate students in nursing in the context of basic care.…”
Section: Assistência Psiquiátrica Através Da Divisão De Saúde Mental mentioning
confidence: 99%
“…With regard to places of practice, training continues to take place predominantly in psychiatric hospitals and alone in outpatient clinics. There were already incipient questions from some professors about the possibility of providing mental health care without isolation of the individual from their family and from their own environment (13,20,26,28,33) . Regarding the contents, the discipline of psychiatric nursing prioritized the study of psychopathologies with a focus on normal and pathological, maintaining a stigmatizing practice (6,13,17,30,39) .…”
Section: Psychiatric Nursing and Mental Health Teaching: The 1972 Curmentioning
confidence: 99%
See 1 more Smart Citation
“…26 In view of this situation, it is possible to criticize the problems related to the academic mental health training, which, together with the discriminatory and exclusivist social conception, lead to the nurses' lack of preparation for providing mental healthcare. 26 It has been observed that, even in the possibility of providing healthcare in primary healthcare units, in accordance with the Systematization of Qualified Nursing Care, and offering the necessary healthcare to meet the complaints of individuals with mental disorders, referral has commonly been the first action. It is important to emphasize that this action should only be considered in the impossibility of providing the necessary healthcare to the patients.…”
Section:  Healthcare Provided By Nurses To Individuals With Mental Dmentioning
confidence: 99%